A diet rich in Mailllard reaction products protects LDL against copper induced oxidation ex vivo, a human intervention trial - Dittrich, Ralf; Dragonas, Charalampos; Kannenkeril, Dennis; Hoffmann, Inge; Müller, Andreas; Beckmann, Matthias; Pischetsrieder, Monika (Food Research International, 2009)
Maillard reaction products (MRPs) have antioxidative properties in vitro but the influence of a diet rich in MRPs on oxidative damage in vivo remains unknown. In this study, the influence of thermally processed foods rich in MRPs on copper induced oxidation of human low-density lipoprotein (LDL) in vitro was examined. Moreover, oxidative resistance of LDL (OR) in blood plasma of eight healthy subjects was monitored, who consumed diets poor and rich in MRPs in weekly turn for 3 weeks. Dark beer, bread crust, and roasted coffee led to a statisticaIly significant increased OR in vitro compared to pale beer, bread crumb, and raw coffee. The consumption of a diet rich in MRPS significantly increased plasma OR compared to the diet poor in MRPs by 35.5%. This study indicates that thermally processed foods rich in MRPs inhibit the LDL oxidation in vitro and have the ability to reduce oxidative modification of LDL in viv
UnivIS-Import:2015-04-14:Pub.2009.nat.dchph.llmch.adietr
Keywords: Beer; Coffee; Diet; LDL oxidation; Maillard reaction products

Angiotensin pathways under therapy with empagliflozin in patients with chronic heart failure - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Rauh, Manfred; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2023)
Aims: Large outcome studies demonstrated a reduction of heart failure hospitalization or cardiovascular death in patients with chronic heart failure (CHF). The renin–angiotensin system (RAS) is a key player in fluid and sodium regulation. The classic angiotensin-converting enzyme–angiotensin II–angiotensin-1 receptor axis (Ang I–ACE–Ang II receptor axis) is predominantly angiotensin II (Ang-II) induced and promotes vasoconstriction. In contrast, the angiotensin-converting-enzyme-2–angiotensin-(1-7)–Mas axis (Mas-axis) is mediated by the metabolites angiotensin-1-7 (Ang-(1-7)) and angtiotensin-1-5 (Ang-(1-5)) and exerts cardioprotective effects. Methods: We previously investigated the effect of empagliflozin on the systemic haemodynamic in patients with stable CHF (NYHA II–III) in a randomized placebo-controlled clinical trial ‘Analysing the Effect of Empagliflozin on Reduction of Tissue Sodium Content in Patients With Chronic Heart Failure (ELSI)’. In a post hoc analysis, we now analysed whether empagliflozin has an effect on the RAS by measuring detailed RAS profiles (LC-MS/MS-based approach) in 72 patients from ELSI. We compared RAS parameters after 1-month and 3-months treatment with empagliflozin or placebo to baseline. The secondary goal was to analyse whether the effect of empagliflozin on RAS parameters was dependent on angiotensin-receptor-blocking (ARB) or angiotensin-converting-enzyme-inhibitor (ACEI) co-medication. Results: Empagliflozin medication induced a significant rise in Ang-II [68.5 pmol/L (21.3–324.2) vs. 131.5 pmol/L (34.9–564.0), P = 0.001], angiotensin-I (Ang-I) [78.7 pmol/L (21.5–236.6) vs. 125.9 pmol/L (52.6–512.9), P < 0.001], Ang-(1-7) [3.0 pmol/L (3.0–15.0) vs. 10.1 pmol/L (3.0–31.3), P = 0.006], and Ang-(1-5) [5.4 pmol/L (2.0–22.9) vs. 9.9 pmol/L (2.8–36.4), P = 0.004], which was not observed in the placebo group (baseline to 3-months treatment). A significant rise in Ang-II (206.4 pmol/L (64.2–750.6) vs. 568.2 pmol/L (164.7–1616.4), P = 0.001), Ang-(1-7) (3.0 pmol/L (3.0–14.1) vs. 15.0 pmol/L (3.0–31.3), P = 0.017), and Ang-(1-5) [12.2 pmol/L (3.8–46.6) vs. 36.4 pmol/L (11.1–90.7), P = 0.001] under empagliflozin treatment was only seen in the subgroup of patients with ARB co-medication, whereas no change of Ang-II (16.7 pmol/L (2.0–60.8) vs. 26.4 pmol/L (10.7–63.4), P = 0.469), Ang-(1-7) (6.6 pmol/L (3.0–20.7) vs. 10.5 pmol/L (3.0–50.5), P = 0.221), and Ang-(1-5) (2.7 pmol/L (2.0–8.4) vs. 2.8 pmol/L (2.0–6.9), P = 0.851) was observed in patients with empagliflozin that were on ACEI co-medication (baseline to 3-months treatment). Conclusions: Our data indicate that empagliflozin might lead to an activation of both the Ang I–ACE–Ang II receptor axis and the Mas-axis pathway. Activation of the Ang I–ACE–Ang II receptor axis and the protective Mas-axis pathway after initiating treatment with empagliflozin was only seen in patients with ARB co-medication, in contrast to co-medication with ACEI.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Angiotensin profiles; Cardioprotective effects; Chronic heart failure; Empagliflozin; Renin–angiotensin system

ANGIOTENSIN PROFILES IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES WITH COMBINATION THERAPY OF EMPAGLIFLOZIN AND LINAGLIPTIN VERSUS METFORMIN AND INSULIN GLARGINE - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Ott, Christian; Pietschner, Robert; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2022-07-29

ANGIOTENSIN PROFILES IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES WITH COMBINATION THERAPY OF EMPAGLIFLOZIN AND LINAGLIPTIN VERSUS METFORMIN AND INSULIN GLARGINE - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Ott, Christian; Pietschner, Robert; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: The renin-angiotensin system (RAS) plays a key role in the physiological regulation of blood pressure. Patients with type-2-diabetes-mellitus (T2DM) and hypertension are known to have increased RAS activity. However, the precise role of RAS activation after SGLT2-inhibitor therapy is unknown. The classic RAS comprises the ACE-AngII-AT1R-axis (classic-axis) that promotes vasoconstriction. The Angiotensin-converting-enzyme-2-angiotensin-(1-7)-Mas axis (Mas-axis) with its components Angiotensin-(1-7) (Ang-1-7) and Angiotensin-(1-5) (Ang-1-5) is an endogenous negative regulatory pathway of the classic-axis, which can reduce its harmful effects. DESIGN AND METHOD: Angiotensin profiles were determined in 55 patients with hypertension and T2DM from our double blind, randomized, placebo controlled clinical trial "Effects of Empagliflozin+Linagliptin (E+L) vs Metformin+Insulin Glargine (M+I) on Renal and Vascular Changes in Type 2 Diabetes'' (ELMI) at baseline and three months after application of either E+L or M+I. An LC-MS/MS based approach was used to simultaneously quantify individual angiotensin metabolites (Attoquant Diagnostics, Vienna, Austria). RESULTS: In the E+L group medication induced a rise in Ang-I, Ang-(1-7) and a trend to a rise in Ang-II between baseline and treatment, which was not present in the M+I group (table).Comparison between the E+L and M+I group revealed that change between baseline and treatment was significantly different for Ang I (p = 0.002) and Ang-(1-7) (p = 0.002) between the groups. No difference in change between baseline and treatment was found for Ang II (p = 0.182) and Ang-(1-5) (p = 0.224) between the E+L and M+I group. CONCLUSIONS: In patients with hypertension and T2DM three months of therapy with E+L led to a rise of classic and protective components of the RAS, which was not present in the M+I group. The biological consequence of this complex RAS activation remains to be elucidated.
CRIS-Team Scopus Importer:2022-09-09

Angiotensin profiles in patients with type 2 diabetes and combination therapy of empagliflozin and linagliptin versus metformin and insulin glargine - Bosch, Agnes; Poglitsch, M.; Kannenkeril, Dennis; Ott, Christian; Striepe, Kristina; Schmieder, Roland (DIABETOLOGIA, 2021)
CRIS-Team WoS Importer:2021-10-01

ANNOYANCE DUE TO NOISE TRIGGERS VASCULAR CHANGES IN THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Harazny, Joanna M.; Striepe, Kristina; Karg, Marina V.; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Association of Noise Annoyance with Measured Renal Hemodynamic Changes - Kannenkeril, Dennis; Jung, Susanne; Ott, Christian; Striepe, Kristina; Kolwelter, Julie; Schmieder, Roland; Bosch, Agnes (Kidney & Blood Pressure Research, 2021)
Background: Chronic mental stress is recognized as a modifiable risk factor for cardiovascular disease. The aim of this study was to demonstrate that noise annoyance-induced stress is associated with changes in renal hemodynamics. Methods: Renal hemodynamic parameters were measured using steady-state input clearance with infusion of para-aminohippuric acid and inulin in individuals with normal, high normal, and elevated blood pressure. All individuals ranked subjective annoyance due to noise in everyday life on a 7-grade Likert scale. The median of all rankings was used as a cutoff point to divide the group into noise-annoyed and non-noise-annoyed individuals. Different renal hemodynamic parameters were calculated based on the Gomez equation. Results: Noise-annoyed individuals (n = 58) showed lower renal plasma flow (599 +/- 106 vs. 663 +/- 124 mL/min, p = 0.009), lower renal blood flow (1,068 +/- 203 vs. 1,172 +/- 225 mL/min, p = 0.047), higher filtration fraction (22.7 +/- 3.3 vs. 21.3 +/- 3.0, p = 0.012), higher renal vascular resistance (88.9 +/- 25.6 vs. 75.8 +/- 22.9 mm Hg/[mL/min], p = 0.002), and higher resistance of afferent arteriole (2,439.5 +/- 1,253.4 vs. 1,849.9 +/- 1,242.0 dyn s(-1) cm(-5), p = 0.001) compared to non-noise-annoyed individuals (n = 55). There was no difference in measured glomerular filtration rate (133 +/- 11.8 vs. 138 +/- 15 mL/min, p = 0.181), resistance of efferent arteriole (2,419.4 +/- 472.2 vs. 2,245.8 +/- 370.3 dyn s(-1) cm(-5), p = 0.060), and intraglomerular pressure (64.0 +/- 3.1 vs. 64.6 +/- 3.5 mm Hg, p = 0.298) between the groups. After adjusting for age, renal plasma flow, renal blood flow, and renal vascular resistance remained significantly different between the groups, with a trend in increased afferent arteriolar resistance and filtration fraction. Conclusion: In this study, noise annoyance was associated with reduced renal perfusion attributed to increased renal vascular resistance predominantly at the afferent site. Long-term consequences of this renal hemodynamic pattern due to noise annoyance need to be investigated.
CRIS-Team WoS Importer:2021-05-14

Blood pressure reduction after renal denervation in patients with or without chronic kidney disease - Günes-Altan, Merve; Schmid, Axel; Ott, Christian; Bosch, Agnes; Pietschner, Robert; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (Clinical Kidney Journal, 2024)
Background. Renal denervation (RDN) has emerged as an adjacent option for the treatment of hypertension. This analysis of the Erlanger registry aimed to compare the blood pressure (BP)-lowering effects and safety of RDN in patients with and without chronic kidney disease (CKD). Methods. In this single-center retrospective analysis, 47 patients with and 127 without CKD underwent radiofrequency-, ultrasound- or alcohol-infusion-based RDN. Office and 24-h ambulatory BP and estimated glomerular filtration rate (eGFR) were measured at baseline, and after 6 and 12 months. Results. A total of 174 patients with a mean age of 59.0 ± 10 years were followed up for 12 months. At baseline, mean eGFR was 55.8 ± 21 mL/min/1.73 m2 in patients with CKD and 87.3 ± 13 mL/min/1.73 m2 in patients without CKD. There was no significant eGFR decline in either of the groups during 12 months of follow-up. In patients without CKD, office systolic and diastolic BP were reduced by –15.3 ± 17.5/–7.9 ± 10.8 mmHg 6 months after RDN and by –16.1 ± 18.2/–7.7 ± 9.6 mmHg 12 months after RDN. In patients with CKD, office systolic and diastolic BP were reduced by –10.7 ± 24.0/–5.8 ± 13.2 mmHg 6 months after RDN and by –15.1 ± 24.9/–5.9 ± 12.9 mmHg 12 months after RDN. Accordingly, in patients without CKD, 24-h ambulatory systolic and diastolic BP were reduced by –7.2 ± 15.8/–4.9 ± 8.8 mmHg 6 months after RDN and by –9.0 ± 17.0/–6.2 ± 9.8 mmHg 12 months after RDN. In patients with CKD, 24-h systolic and diastolic BP were reduced by –7.4 ± 12.9/–4.2 ± 9.9 mmHg 6 months after RDN and by –8.0 ± 14.0/–3.6 ± 9.6 mmHg 12 months after RDN. There was no difference in the reduction of office and 24-h ambulatory BP between the two groups at any time point (all P > .2). Similar results have been found for the 6 months data. With exception of rare local adverse events, we did not observe any safety signals. Conclusion. According to our single-center experience, we observed a similar reduction in 24-h, day and night-time ambulatory BP as well as in-office BP in patients with and without CKD at any time point up to 12 months. We conclude that RDN is an effective and safe treatment option for patients with hypertension and CKD.
CRIS-Team Scopus Importer:2024-01-26
Keywords: blood pressure; chronic kidney disease; hypertension; post-hoc analysis; renal denervation

BLOOD PRESSURE REDUCTION AFTER RENAL DENERVATION IN PATIENTS WITH OR WITHOUT CHRONIC KIDNEY DISEASE: THE ERLANGER EXPERIENCE - Schmid, Axel; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (JOURNAL OF HYPERTENSION, 2023)
CRIS-Team WoS Importer:2023-03-17

CAN WE IDENTIFY GLOMERULAR HYPERFILTRATION IN PATIENTS WITH TYPE 2 DIABETES BY CLINICAL PARAMETERS? - Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Jung, Susanne; Bosch, Agnes; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Capillary vascular density in the retina of hypertensive patients is associated with a non-dipping pattern independent of mean ambulatory blood pressure - Nolde, Janis M.; Frost, Shaun; Kannenkeril, Dennis; Lugo-Gavidi, Leslie Marisol; Chan, Justine; Joyson, Anu; Azzam, Omar; Carnagarin, Revathy; Kiuchi, Marcio G.; Vignarajan, Janardhan; Schlaich, Markus P. (Journal of Hypertension, 2021)
Background: A nocturnal non-dipping pattern has been associated with hypertension-mediated organ damage (HMOD), morbidity and mortality. Retinal imaging through application of modern technologies including optical coherence tomography angiography (OCT-A) can provide detailed insights into early vascular damage. In this observational study, we investigated the relationship of microscopic vascular density in the retina measured with OCT-A and nocturnal blood pressure (BP) dipping.
CRIS-Team WoS Importer:2021-08-20

CAPILLARY VASCULAR DENSITY IN THE RETINA OF HYPERTENSIVE SUBJECTS IS ASSOCIATED WITH A NON-DIPPING PATTERN INDEPENDENT OF MEAN AMBULATORY BLOOD PRESSURE - Nolde, J. M.; Frost, S.; Kannenkeril, Dennis; Lugo-Gavidia, L. M.; Chan, J.; Joyson, A.; Azzam, O.; Carnagarin, R.; Kiuchi, M. G.; Vignarajan, J.; Schlaich, M. P. (ATHEROSCLEROSIS, 2021)
CRIS-Team WoS Importer:2021-09-24

Change of renal function after short-term use of cardioprotective agents in patients with type 2 diabetes is not accurately assessed by the change of estimated glomerular filtration rate: an observational study - Kolwelter, Julie; Striepe, Kristina; Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Schiffer, Mario; Schmieder, Roland (Diabetology & Metabolic Syndrome, 2022)
Background After initiating cardioprotective agents, a fall of estimated glomerular filtration rate (eGFR) has been reported in several studies. Our goal was to evaluate the accuracy of change of Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) eGFR in patients with type 2 diabetes (T2D) after short-term pharmacological intervention with angiotensin-converting enzyme inhibitor, angiotensin-receptor blocker, gliptin or sodium-glucose cotransporter-2 inhibitor. Methods We analyzed 190 patients with T2D in the early stage of the disease, having no overt renal impairment by CKD-EPI equation. In each patient, we measured GFR (mGFR) by applying the constant infusion input clearance technique with sinistrin (Inutest; Fresenius, Linz, Austria) at baseline and after short-term (4-12 weeks) pharmacological intervention with cardioprotective agents (ramipril, telmisartan, linagliptin, metformin, empagliflozin) that potentially lead to an alteration of renal function. Simultaneously, a standardized analysis of serum creatinine was performed and eGFR was estimated by the CKD-EPI equation. Results Average mGFR was 111 +/- 20 ml/min/1.73m(2), whereas eGFR was lower with 93 +/- 13 ml/min/1.73m(2). The ratio eGFR/mGFR in relation to mGFR was almost curvilinear, showing an underestimation of renal function by eGFR in the upper normal range. At baseline only 80 patients (42%) lay within +/- 10% of mGFR and the concordance correlation coefficient (CCC) was extremely low (- 0.07). After short-term pharmacological intervention changes in eGFR and mGFR correlated with each other (r = 0.286, p < 0.001). For example, for a given mGFR of 111 ml/min/1.73m(2), a change of mGFR by +/- 10% corresponded to +/- 11 ml/min/1.73m(2), but the confidence interval of eGFR was 25 ml/min/1.73m(2). The CCC was low (0.22). Conclusion The agreement between eGFR by CKD-EPI and mGFR is modest and the change of renal function after short-term pharmacological intervention is not accurately and precisely reflected by the change of eGFR in patients with T2D in the early stage of their disease.
CRIS-Team WoS Importer:2022-08-05

Combination of empagliflozin and linagliptin improves blood pressure and vascular function in type 2 diabetes - Jung, Susanne; Bosch, Agnes; Kannenkeril, Dennis; Karg, Marina V.; Striepe, Kristina; Bramlage, Peter; Ott, Christian; Schmieder, Roland; Jung, Susanne (European Heart Journal - Cardiovascular Pharmacotherapy, 2020)
AIMS: Preserved vascular function represents a key prognostic factor in type 2 diabetes mellitus (T2DM), but data on vascular parameters in this patient cohort are scarce. Patients with T2DM often need more than one drug to achieve optimal glucose control. The aim of this study was to analyse the efficacy of two combination therapies on vascular function in subjects with T2DM. METHODS AND RESULTS: This prospective, randomized study included 97 subjects with T2DM. Subjects were randomized to either the combination therapy empagliflozin (E) 10 mg with linagliptin (L) 5 mg once daily or metformin (M) 850 or 1000 mg twice daily with insulin glargine (I) once daily. At baseline and after 12 weeks, subjects had peripheral office and 24-h ambulatory blood pressure (BP) measurement and underwent vascular assessment by pulse wave analysis under office and ambulatory conditions. Office, 24-h ambulatory and central BP as well as pulse pressure (PP) decreased after 12 weeks of treatment with E + L, whereas no change was observed in M + I. There were greater decreases in 24-h ambulatory peripheral systolic (between-group difference: -5.2 ± 1.5 mmHg, P = 0.004), diastolic BP (-1.9 ± 1.0 mmHg, P = 0.036), and PP (-3.3 ± 1.0 mmHg, P = 0.007) in E + L than M + I. Central office systolic BP (-5.56 ± 1.9 mmHg, P = 0.009), forward pressure height of the pulse wave (-2.0 ± 0.9 mmHg, P = 0.028), 24-h ambulatory central systolic (-3.6 ± 1.4 mmHg, P = 0.045), diastolic BP (-1.95 ± 1.1 mmHg, P = 0.041), and 24-h pulse wave velocity (-0.14 ± 0.05m/s, P = 0.043) were reduced to a greater extent with E + L. CONCLUSION: Beyond the effects on glycaemic control, the combination therapy of E + L significantly improved central BP and vascular function compared with the classic combination of M + I. CLINICALTRIALS.GOV: NCT02752113.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Blood pressure; Central haemodynamics; Empagliflozin; Linagliptin; T2DM; Vascular function

Combined therapy of empagliflozin and linagliptin is superior to metformin and insulin glargine in improving blood pressure and vascular function in type 2 diabetes - Jung, Susanne; Bosch, Agnes; Kannenkeril, Dennis; Karg, M.; Striepe, Kristina; Bramlage, P.; Ott, Christian; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

COPEPTIN AS A RESEARCH MARKER IN CARDIOVASCULAR DISEASE - Bosch, Agnes; Ott, C.; Schmid, Andrea; Kannenkeril, Dennis; Karg, M.; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2018)
EVALuna2:202963

COPEPTIN LEVELS IN PATIENTS WITH TREATMENT RESISTANT HYPERTENSION BEFORE AND AFTER RENAL DENERVATION - Jumar, A.; Ott, Christian; Schmid, Axel; Kannenkeril, Dennis; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36267

Copeptin levels in patients with treatment resistant hypertension before and six months after renal denervation - Bosch, Agnes; Schmid, Axel; Ott, Christian; Kannenkeril, Dennis; Karg, Marina V.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (American Journal of Hypertension, 2019)
BACKGROUND: Copeptin, the C-terminal peptide of pro-vasopressin, is released from the neurohypophysis and reflects the activity of the hormone arginine vasopressin in patients with hypertension. Elevated copeptin levels are associated with increased cardiovascular and all-cause mortality. The aim of this study is to compare copeptin levels in patients with treatment resistant hypertension (TRH) before and 6 months after renal denervation (RDN). METHODS: Copeptin was measured in 34 patients with TRH and 30 patients with primary hypertension stage 1 or 2 (HT). In addition, copeptin levels were measured in patients with TRH at 6 month follow-up visit after RDN. RDN was performed by an experienced interventionalist applying at least four ablations longitudinally and rotationally within the lengths of each renal artery to cover a full four quadrant ablation. RESULTS: In patients with TRH 24h ambulatory blood pressure (BP) decreased from 154±15/ 87±12 mmHg to 146±13/ 83±7.9 mmHg after RDN (systolic: p=0.001, diastolic: p=0.034). There was no significant change in copeptin levels in these 34 patients with TRH before versus six months after RDN (median 8.4 [interquartile range 3.6-14] vs 8.5 [4.5-13] pmol/l, p=0.334). Patients with TRH had higher copeptin levels (p=0.024) than patients with HT (24h ambulatory BP: 142±11/ 91±8.3 mmHg, copeptin: 4.2 [2.8-6.3] pmol/l). CONCLUSION: Patients with TRH showed 2 fold higher copeptin levels than patients with HT. RDN did not lead to any change of copeptin levels in patients with TRH 6 months after procedure despite significant fall in BP.
EVALuna2:210911

Dependency of flow-mediated vasodilatation from basal nitric oxide activity - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Jung, Susanne; Striepe, Kristina; Ott, Christian; Delles, Christian; Schmieder, Roland (Clinical Physiology and Functional Imaging, 2021)
Background: Flow-mediated vasodilatation (FMD) has become one of the most widely assessed parameters to analyse endothelial and vascular function in cardiovascular medicine. The degree of contribution of nitric oxide (NO) to FMD is inconclusive and varies widely depending on the device used. In this study, we used a semi-automatic ultrasound device to analyse to what extent basal NO activity contributes to FMD of the brachial artery. Methods: FMD was assessed with the UNEX EF device in a cross-over single blinded randomized study at baseline and then during infusion of either a NO-synthase-inhibitor (NG-monomethyl-L-arginine (L-NMMA)) or saline. The analysis was repeated after 1 week with the alternative infusion of L-NMMA or saline. All measurements were analysed both automatically and by a technician manually. Results: In total, 25 healthy men subjects completed the study. Diastolic blood pressure and heart rate significantly changed during infusion of L-NMMA. Infusion of L-NMMA reduced FMD significantly (−37%, p = 0.002). Saline solution had no effect on FMD (+14%, p = 0.392). Change in FMD was significantly different between the groups (ΔFMDL-NMMA vs. ΔFMDsaline, p = 0.032). There was a statistically significant correlation between automatically analysed results and those obtained by an experienced technician (FMDsaline: r = 0.822, p < 0.001; FMDL-NMMA: r = 0.645, p = 0.007). Conclusion: The influence of NO on FMD is approximately 40% if assessed using the UNEX EF. Prior to use FMD as a marker of endothelial dysfunction, we should explore different methods including various duration of forearm ischaemia to increase NO dependency of FMD.
CRIS-Team Scopus Importer:2021-04-02
Keywords: basal nitric oxide activity; flow-mediated vasodilatation; UNEX EF

DETAILED ANALYSIS OF VASCULAR STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Kannenkeril, Dennis; Ott, Christan; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2022-07-29

DETAILED ANALYSIS OF VASCULAR STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Kannenkeril, Dennis; Ott, Christan; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Risk factors for chronic heart failure (CHF) lead as well to vascular stiffness of the large arteries, increasing thereby the afterload imposed on the left ventricle and deteriorating the clinical condition of CHF. The aim of this project was twofold: to compare vascular stiffness of patients with CHF (CHF+) to those without CHF (CHF-) and to analyse whether vascular stiffness is related to the severity of CHF. DESIGN AND METHOD: In this cross-sectional project a total of 223 patients were included (CHF+: n = 105, CHF-: n = 118). Patients in an euvolaemic state with a reduced left ventricular ejection fraction (LVEF) were included in the CHF+ group. The measurement of the pulse wave velocity (PWV), the most accepted vascular stiffness parameter, and the recording of the arterial pulse wave were performed using the SphygmoCor TM XCEL System under resting conditions. Under ambulatory conditions, blood pressure (BP) and vascular stiffness parameters were assessed by a validated device (Mobil-O-Graph, I.E.M.) over 24 hours. Additionally, blood and spot urine samples were used to measure laboratory markers, in particular NT-pro-BNP. RESULTS: Vascular stiffness parameters between the CHF+ and the CHF- group differed for resting central SBP (CHF+: 116.66 ± 15.18 mmHg, CHF-: 122.83 ± 15.87 mmHg, p = 0.004) and central augmentation index (CHF+: 21.24 ± 11.76 %, CHF-: 13.69 ± 11.49 %, p = <0.001) as well as for ambulatory central SBP (CHF+: 114.46 ± 15.35 mmHg, CHF-: 120.69 ± 13.97 mmHg, p = 0.007) and PWV (CHF+: 9.39 ± 1.56 m/s, CHF-: 8.19 ± 1.65 m/s, p = <0.001). In patients with CHF, greater levels of NT-pro-BNP were related to a higher central SBP (r = 0.292, p = 0.005), higher PWV (r = 0.340, p = <0.001) and a trend to higher central PP (r = 0.198, p = 0.058), after full adjustment for CHF risk factors and gender. In accordance, higher levels of NT-pro-BNP were related to a higher ambulatory peripheral PP (r = 0.322, p = 0.002) and total peripheral resistance (r = 0.227, p = 0.041). CONCLUSIONS: In patients with stable CHF we observed a worse vascular stiffness and function, compared to patients with no CHF. The extent of vascular stiffness and dysfunction was related to the severity of CHF.
CRIS-Team Scopus Importer:2022-09-09

Detection of Changes in Renal Blood Flow Using Arterial Spin Labeling MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (American Journal of Nephrology, 2021)
Background: Alteration in kidney perfusion is an early marker of renal damage. The purpose of this study was to evaluate if changes in renal blood flow (RBF) could be detected using MRI with arterial spin labeling (ASL) technique. Methods: RBF as assessed by cortical (CRBF), medullary, and total renal blood flow (TRBF) were measured by MRI with arterial spin labeling (ASL-MRI) using flow-sensitive alternating inversion recovery true fast imaging with steady-state precession sequence. In 11 normotensive healthy individuals (NT) and 11 hypertensive patients (HT), RBF was measured at baseline and after both feet were covered with cold ice packs (cold pressor test) that activates the sympathetic nervous system. In another experiment, RBF was measured in 10 patients with CKD before and after a pharmacological intervention. We compared RBF measurements between the 3 study populations. Results: A significant reduction in CRBF (p = 0.042) and a trend in TRBF (p = 0.053) were observed in response to the activation of the sympathetic nervous system. A trend toward reduction of CRBF (p = 0.051) and TRBF (p = 0.059) has been detected after pharmacological intervention. TRBF was significantly lower in patients with HT and CKD patients compared to NT individuals (NT vs. HT, p = 0.014; NT vs. CKD, p = 0.004). TRBF was lower in patients with CKD compared to HT (p = 0.047). Conclusion: Our data indicate that both acute and short-term changes in RBF could be detected using ASL-MRI. We were able to detect differences in RBF between healthy and diseased individuals by needing only small sample size per group. Thus, ASL-MRI offers an advantage in conducting clinical trials compared to other technologies.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ASL-MRI; Cold pressor test; Renal blood flow

DETECTION OF CHANGES IN RENAL BLOOD FLOW USING ARTERIAL SPIN LABELING MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Determinants of arterial stiffness in patients with type 2 diabetes mellitus: a cross sectional analysis - Staef, Mawadah; Ott, Christian; Kannenkeril, Dennis; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland; Bosch, Agnes (Scientific Reports, 2023)
In patients with type 2 diabetes mellitus (T2DM) arterial stiffness is associated with increased cardiovascular and total mortality. Little is known about determinants of arterial stiffness in clinical routine. Identification of potential determinants of arterial stiffness will help to address treatment targets for patients in the early state of T2DM. This is a cross-sectional analysis of arterial stiffness in 266 patients in the early stage of T2DM who did not have cardiovascular or renal complications. Parameters of arterial stiffness such as central systolic blood pressure (cSBP), central pulse pressure (cPP) and pulse wave velocity (PWV) were measured with the SphygmoCor System (AtCor Medical). We investigated the influence of parameters of glucose metabolism, lipid status, body constitution, blood pressure (BP) and inflammation on the stiffness parameters using multivariate regression analysis. The study cohort consisted of male and female patients aged 61 ± 8 years with mean diabetes duration of 6.4 ± 5.1 years, mean HbA1c 7.1 ± 0.9%, mean cSBP 121 ± 12 mmHg, mean cPP 44 ± 10 mmHg and mean PWV 8.9 ± 1.8 m/s. Multiple regression analysis identified waist circumference (WC) (beta = 0.411, p = 0.026), LDL-cholesterol (beta = 0.106, p = 0.006), systolic office BP (beta = 0.936, p < 0.001) and diabetes duration (beta = 0.233, p = 0.043) as potential determinants of cSBP. cPP was determined by sex (beta = 0.330, p = 0.008), age (beta = 0.383, p < 0.001), systolic office BP (beta = 0.370, p < 0.001) and diabetes duration (beta = 0.231, p = 0.028) whereas for PWV the following determinants could be identified: age (beta = 0.405, p < 0.001), systolic office BP (beta = 0.421, p < 0.001) and diabetes duration (beta = 0.073, p = 0.038). In addition to the known parameters age, sex and systolic office BP serum LDL-cholesterol, WC and diabetes duration have been identified as determinants of arterial stiffness in patients with T2DM. Treatment of patients in the early stage of T2DM should focus on these clinical parameters to prevent progression of arterial stiffness and as a consequence reduce cardiovascular mortality. Trial registration: The patients included in the analysis participated in one of the following clinical trials NCT02752113 (registered 26.4.2016), NCT02383238 (09.03.2015), NCT02471963 (15.06.2015), NCT01319357 (21.03.2011) (http://www.clinicaltrials.gov).
CRIS-Team Scopus Importer:2023-06-30

DIFFERENT RESPONSE PATTERN TO AIRCRAFT NOISE EXPOSURE IN RENAL VERSUS SYSTEMIC HEMODYNAMIC - Bosch, Agnes; Ott, C.; Kannenkeril, Dennis; Harazny, J. M.; Striepe, Kristina; Karg, M.; Dienemann, T.; Jung, Susan; Schmieder, Roland (2018)
EVALuna2:202964

Disparate effects of the combined therapy of empagliflozin and linagliptin versus metformin and insulin glargine on renal haemodynamics in type 2 diabetes - Ott, Christian; Jung, Susan; Kannenkeril, Dennis; Striepe, Kristina; Bosch, Agnes; Korn, M.; Bramlage, P.; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

DISPARATE NITRIC OXIDE ACTIVITY OF THE RETINAL CIRCULATION IN HYPERTENSIVE VS TYPE 2 DIABETES-PATIENTS - Kannenkeril, Dennis; Jung, Susan; Harazny, J. M.; Bosch, Agnes; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Early vascular parameters in the micro- and macrocirculation in type 2 diabetes - Kannenkeril, Dennis; Bosch, Agnes; Harazny, Joanna; Karg, Marina; Jung, Susan; Ott, Christian; Schmieder, Roland (Cardiovascular Diabetology, 2018)
BACKGROUND: Diabetes converts from a metabolic disorder into a predominantly vascular disease, once its duration extends over several years or/and when additional cardiovascular risk factors such as hypertension coexist. In a cross-sectional analysis we analyzed various vascular parameters in the renal, retinal and systemic circulation, with the goal to identify which vascular parameter of early organ damage is the earliest that can be clinically detected. METHODS: In 111 patients with type 2 diabetes (T2DM) (off any anti-diabetic medication for at least 4 weeks) and 54 subjects without T2DM we compared various parameters of early vascular remodeling in the same patient: urinary albumin creatinine ratio ([UACR], early morning spot urine) and estimated glomerular filtration rate (eGFR), retinal capillary flow (RCF) and intercapillary distance (ICD) as parameters of capillary rarefaction, wall-to-lumen ratio (WLR) of the retinal arterioles [all assessed by Scanning Laser Doppler Flowmetry], and central systolic pressure (cSBP) and central pulse pressure (cPP) [measured by pulse wave analysis, Syphygmocor] both reflecting vascular stiffness of large arteries. RESULTS: Compared to subjects without T2DM, patients with T2DM (diabetes duration: median 48 months, interquartile range 24-88 months) were older (59.8 ± 7.3 vs 43.4 ± 12.9 years, p < 0.001), more females (33.3 vs 20.4%, p < 0.001), but 24-h systolic and diastolic blood pressure did not differ between the two groups. The analysis adjusted for age, gender and cardiovascular risk factors revealed that ICD (23.9 ± 5.1 vs 20.8 ± 3.5 µm, p value = 0.001) and cPP (41.8 ± 11.7 vs 34.8 ± 10.6 mmHg, p value < 0.001) were significantly higher and eGFR (91.7 ± 9.9 vs 95.9 ± 17.3 ml/min/1.73 m2, p value < 0.001) was significantly lower in patients with T2DM than in subjects without T2DM. CONCLUSION: These data suggest that at similar blood pressure capillary rarefaction in the retinal circulation (ICD), decreased eGFR in the renal circulation and increased central pulse pressure (cPP) of large arteries are earlier detectable than other vascular remodeling parameters of the micro- (WLR, RCF, UACR) and macrocirculation (cSBP) in patients with T2DM. Trial registration Trial registration number: NCT02471963, Date of registration: June 15, 2015, retrospectively registered; Trial registration number: NCT01319357, Date of registration: March 21, 2011, retrospectively registered; Trial registration number: NCT02383238, Date of registration: March 9, 2015, retrospectively registered; Trial registration number: NCT00152698, Date of registration: September 9, 2005, prospectively registered; Trial registration number: NCT00136188, Date of registration: August 26, 2005, prospectively registered.
EVALuna2:35230

Effect of empagliflozin on ketone bodies in patients with stable chronic heart failure - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Jung, Susan; Kannenkeril, Dennis; Ott, C.; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Recent studies indicated that sodium glucose cotransporter (SGLT)2 inhibition increases levels of ketone bodies in the blood in patients with type 1 and 2 diabetes. Other studies suggested that in patients with chronic heart failure (CHF), increased myocardial oxygen demand can be provided by ketone bodies as a fuel substrate. Experimental studies reported that ketone bodies, specifically beta-hydroxybutyrate (β-OHB) may increase blood pressure (BP) by impairing endothelium-dependant relaxation, thereby leading to increased vascular stiffness. In our study we assessed whether the SGLT 2 inhibition with empagliflozin increases ketone bodies in patients with stable CHF and whether such an increase impairs BP and vascular function. Methods: In a prospective, double blind, placebo controlled, parallel-group single centre study 75 patients with CHF (left ventricular ejection fraction 39.0 ± 8.2%) were randomised (2:1) to the SGLT-2 inhibitor empagliflozin 10 mg orally once daily or to placebo, 72 patients completed the study. After a run-in phase we evaluated at baseline BP by 24 h ambulatory blood pressure (ABP) monitoring, vascular stiffness parameters by the SphygmoCor system (AtCor Medical, Sydney, NSW, Australia) and fasting metabolic parameters, including β-OHB by an enzymatic assay (Beckman Coulter DxC 700 AU). The same measurements were repeated 12 weeks after treatment. In 19 of the 72 patients serum levels of β-OHB were beneath the lower border of our assay (< 0.05 mmol/l) therefore being excluded from the subsequent analysis. Results: In patients with stable CHF, treatment with empagliflozin (n = 36) was followed by an increase of β-OHB by 33.39% (p = 0.017), reduction in 24 h systolic (p = 0.038) and diastolic (p = 0.085) ABP, weight loss (p = 0.003) and decrease of central systolic BP (p = 0.008) and central pulse pressure (p = 0.008). The increase in β-OHB was related to an attenuated decrease of empagliflozin-induced 24 h systolic (r = 0.321, p = 0.069) and diastolic (r = 0.516, p = 0.002) ABP and less reduction of central systolic BP (r = 0.470, p = 0.009) and central pulse pressure (r = 0.391, p = 0.033). No significant changes were seen in any of these parameters after 12 weeks of treatment in the placebo group (n = 17). Conclusion: In patients with stable CHF ketone bodies as assessed by β-OHB increased after treatment with empagliflozin. This increase led to an attenuation of the beneficial effects of empagliflozin on BP and vascular parameters. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT03128528).
CRIS-Team Scopus Importer:2021-11-19

Effect of SGLT2 inhibition on ketone bodies in patients with stable chronic heart failure - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Kannenkeril, Dennis; Ott, C.; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (DIABETOLOGIA, 2021)
CRIS-Team WoS Importer:2021-10-01

EFFECTS OF THE NO SYNTHASE INHIBITOR RONOPTERIN (VAS203) ON MICRO- AND MACROCIRCULATION IN HEALTHY VOLUNTEERS - Ott, Christian; Bosch, Agnes; Jung, Susan; Kannenkeril, Dennis; Schinzel, R.; Tegtmeier, F.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Effects of the Selective Sodium-Glucose Cotransporter 2 Inhibitor Empagliflozin on Vascular Function and Central Hemodynamics in Patients With Type 2 Diabetes Mellitus - Striepe, Kristina; Jumar, Agnes; Ott, Christian; Karg, Margarete; Schneider, Markus; Kannenkeril, Dennis; Schmieder, Roland (Circulation, 2017)
EVALuna2:4021

EFFECTS OF THE SGLT2 INHIBITOR EMPAGLIFLOZIN ON VASCULAR FUNCTION IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Linz, Peter; Kannenkeril, Dennis; Nagel, Armin Michael; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

Effects of the sodium-glucose cotransporter 2 inhibitor empagliflozin on vascular function in patients with chronic heart failure - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Stabel, Lena; Kannenkeril, Dennis; Ott, Christian; Bramlage, Peter; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims Impairment of vascular function contributes to the progression of chronic heart failure (HF) by increasing the afterload. Treatment with selective sodium-glucose cotransporter 2 (SGLT2) inhibitors improves the prognosis of HF, but the precise mechanisms remain unclear. The aim of this study was to analyse the effect of empagliflozin on vascular function in patients with HF.
CRIS-Team WoS Importer:2021-10-01

Effects of treatment with SGLT-2 inhibitors on arginine-related cardiovascular and renal biomarkers - Geßner, Arne; Gemeinhardt, Anna; Bosch, Agnes; Kannenkeril, Dennis; Staerk, Christian; Mayr, Andreas; Fromm, Martin; Schmieder, Roland; Maas, Renke (Cardiovascular Diabetology, 2022)
Background: In patients with type 2 diabetes (T2D) sodium-glucose cotransporter 2 (SGLT-2) inhibitors improve glycaemic control as well as cardiovascular and renal outcomes. Their effects on L-arginine (Arg) related risk markers asymmetric and symmetric dimethylarginine (ADMA and SDMA) and the protective biomarker L-homoarginine (hArg) linking T2D to cardiovascular and renal disease have not yet been reported.
CRIS-Team WoS Importer:2022-01-14

Evidence of neurodegeneration in individuals with only mildly elevated blood pressure - Jung, Susanne; Bosch, Agnes; Kohler, Nikolas; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2019)
OBJECTIVE: Initiation of antihypertensive drug treatment in low-risk individuals with grade 1 hypertension is under debate. The aim of this study was to examine the impact of mildly elevated blood pressure (BP) on early neurodegenerative processes independent of ageing. METHODS: Sixty-two individuals were included in this study: 25 young (aged <40 years) and 37 older (aged ≥40 years) individuals at low cardiovascular risk and grade 1 hypertension at most. Macular retinal layer volumes of both eyes were determined by SD-OCT. Total retinal volume but also each inner retinal layer volume separately including retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), and GCL-IPL were measured in each individual. RESULTS: Retinal layer volumes were lower among older individuals compared with young individuals (RNFL right eye: P = 0.037/left eye: P = 0.021; GCL and GCL-IPL: both eyes P < 0.001; IPL right eye: P = 0.005/left eye: P = 0.002; total retinal volume: both eyes P = 0.002) and there was an inverse correlation between retinal layer volumes and age. Partial correlation analysis, excluding age as a cofactor, revealed an inverse association between retinal layer volumes and DBP. In multiple regression analysis, DBP was identified as a determinant of retinal neurodegenerative processes. CONCLUSION: In the current study, we observed an inverse association between retinal neurodegenerative processes and DBP, suggesting that BP-lowering therapy by early antihypertensive drug-treatment might be beneficial to avoid early neurodegeneration.
EVALuna2:203883

Experience with belatacept rescue therapy in kidney transplant recipients - Brakemeier, Susanne; Kannenkeril, Dennis; Duerr, Michael; Braun, Timm; Bachmann, Friederike; Schmidt, Danilo; Wiesener, Michael; Budde, Klemens (Transplant International, 2016)
In kidney transplant recipients with chronic graft dysfunction, long-term immunosuppression with calcineurin inhibitors (CNIs) or mTOR inhibitors (mTORi) can be challenging due to adverse effects, such as nephrotoxicity and proteinuria. Seventy-nine kidney transplant recipients treated with CNI-based or mTORi-based maintenance immunosuppression who had CNI-induced nephrotoxicity or severe adverse events were switched to belatacept. Mean time from transplantation to belatacept conversion was 69.0 months. Mean estimated glomerular filtration rate (eGFR) ± standard deviation at baseline was 26.1 ± 15.0 ml/min/1.73 m(2) , increasing to 34.0 ± 15.2 ml/min/1.73 m(2) at 12 months postconversion (P < 0.0005). Renal function improvements were also seen in patients with low eGFR (<25 ml/min/1.73 m(2) ) or high proteinuria (>500 mg/l) at conversion. The Kaplan-Meier estimates for patient and graft survival at 12 months were 95.0% and 85.6%, respectively. The discontinuation rate due to adverse events was 7.9%. One case of post-transplant lymphoproliferative disorder occurred at 17 months postconversion. For comparison, a historical control group of 41 patients converted to mTORi-based immunosuppression because of biopsy-confirmed CNI-induced toxicity was examined; eGFR increased from 27.6 ± 7.2 ml/min/1.73 m(2) at baseline to 31.1 ± 11.9 ml/min/1.73 m(2) at 12 months (P = 0.018). Belatacept-based immunosuppression may be an alternative regimen for kidney transplant recipients with CNI- or mTORi-induced toxicity.
EVALuna2:3933

FLOW MEDIATED VASODILATION/VASOCONSTRICTION IN DIFFERENT DISEASE POPULATIONS - Kannenkeril, Dennis; Dienemann, T.; Jung, Susan; Striepe, Kristina; Kopp, C.; Schneider, M.; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

How does empagliflozin improve arterial stiffness in patients with type 2 diabetes mellitus? - Bosch, A.; Ott, Christian; Jung, Susan; Striepe, Kristina; Karg, M. V.; Kannenkeril, Dennis; Dienemann, T.; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

How does empagliflozin improve arterial stiffness in patients with type 2 diabetes mellitus? Sub analysis of a clinical trial - Bosch, Agnes; Ott, Christian; Jung, Susan; Striepe, Kristina; Karg, Marina V.; Kannenkeril, Dennis; Dienemann, Thomas; Schmieder, Roland (Cardiovascular Diabetology, 2019)
BackgroundEmpagliflozin has been shown to reduce cardiovascular mortality, but the underlying pathogenetic mechanisms are poorly understood. It was previously demonstrated that empagliflozin improved arterial stiffness.MethodsOur analysis comprising 58 patients with type 2 diabetes mellitus identifies factors triggering the improvement of arterial stiffness. All patients participated in an investigator-initiated, prospective, double-blind, randomized, placebo-controlled, interventional clinical trial (http://www.ClinicalTrials.gov: NCT02471963, registered 15th June 2015, retrospectively registered) and received either 6-weeks treatment with 25mg empagliflozin orally once daily or placebo (crossover). Central systolic pressure and central pulse pressure were recorded by the SphygmoCor System (AtCor Medical). Now, we investigated the impact of parameters of glucose metabolism, volume status, sympathetic activation, lipids, uric acid, blood pressure and inflammation on vascular parameters of arterial stiffness using multivariate regression analysis.ResultsAs previously reported, therapy with empagliflozin improved arterial stiffness as indicated by reduced central systolic blood pressure (113.612.1 vs 118.612.9mmHg, p<0.001), central pulse pressure (39.1 +/- 10.2 vs 41.9 +/- 10.7mmHg, p=0.027) forward (27.1 +/- 5.69 vs 28.7 +/- 6.23mmHg, p=0.031) as well as reflected wave amplitude (18.9 +/- 5.98 vs 20.3 +/- 5.97mmHg, p=0.045) compared to placebo. The multivariate regression analysis included age, sex and change between empagliflozin and placebo therapy of the following parameters: HbA1c, copeptin, hematocrit, heart rate, LDL-cholesterol, uric acid, systolic 24-h ambulatory blood pressure and high sensitive CRP (hsCRP). Besides the influence of age (beta=-0.259, p=0.054), sex (beta=0.292, p=0.040) and change in systolic 24-h ambulatory blood pressure (beta=0.364, p=0.019), the change of hsCRP (beta=0.305, p=0.033) emerged as a significant determinant of the empagliflozin induced reduction in arterial stiffness (placebo corrected). When replacing HbA1c with fasting plasma glucose in the multivariate regression analysis, a similar effect of the change in hsCRP (beta=0.347, p=0.017) on arterial stiffness parameters was found.Conclusion Besides age and sex, change in systolic 24-h ambulatory blood pressure and change in hsCRP were determinants of the empagliflozin induced improvement of vascular parameters of arterial stiffness, whereas parameters of change in glucose metabolism and volume status had no significant influence. Our analysis suggests that empagliflozin exerts, at least to some extent, its beneficial vascular effects via anti-inflammatory mechanisms.
CRIS-Team WoS Importer:2019-04-18

IMPACT OF BLOOD PRESSURE AND AGEING ON RETINAL NEURODEGENERATION ASSESSED BY SPECTRAL-DOMAIN OPTICAL COHERENCE TOMOGRAPHY - Jung, Susan; Bosch, Agnes; Kohler, N.; Ott, Christian; Kannenkeril, Dennis; Dienemann, T.; Harazny, J. M.; Michelson, Georg; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Increased pulse wave velocity in patients with an orthostatic blood pressure rise independent of other cardiovascular risk factors - Nolde, Janis M.; Lugo-Gavidia, Leslie Marisol; Kannenkeril, Dennis; Chan, Justine; Matthews, Vance B.; Carnagarin, Revathy; Azzam, Omar; Kiuchi, Márcio Galindo; Schlaich, Markus P. (Journal of Hypertension, 2021)
BACKGROUND: Positional changes in blood pressure (BP) have been shown to have effects on long-term outcomes. Although a BP drop with upright posture is frequently observed, an orthostatic rise in BP can also occur. Here, we aimed to investigate whether the phenotype of orthostatic hypertension is associated with more pronounced vascular hypertension-mediated organ damage (HMOD) and whether this is associated with other cardiovascular risk factors. METHODS: In a cohort of 200 patients referred to our tertiary hypertension clinic, we prospectively assessed unattended seated automated office BP and the response to 1 min of upright posture. The difference in BP after standing up was calculated and pulse wave velocity (PWV) was assessed as a marker of vascular HMOD. Routine clinical cardiovascular risk markers were also assessed. Regression models were used to assess the association between orthostatic BP changes and pulse wave velocity. RESULTS: Baseline characteristics and clinic cardiovascular risk factors were similar between orthostatic BP response groups. A U-shaped association was evident between PWV and orthostatic BP changes with elevated PWV in patients with either a fall or a rise in BP in response to upright posture. The regression models remained significant after adjusting for other cardiovascular risk factors, including 24 h ambulatory BP. CONCLUSION: Both an orthostatic BP drop and rise were associated with elevated PWV. Although standing BP is commonly measured in elderly hypertensive patients to exclude significant orthostatic hypotension, this simple measurement may provide an additional independent risk factor for vascular HMOD at any age.
CRIS-Team Scopus Importer:2021-06-18

IS BASAL NITRIC OXIDE ACTIVITY OF THE RENAL VASCULATURE ALTERED? ANALYSIS OF A RANDOMIZED CONTROLLED TRIAL COMPARING TWO COMBINATION THERAPIES - Kannenkeril, Dennis; Ott, Christian; Bosch, Agnes; Striepe, Kristina; Pietschner, Robert; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

IS BASAL NITRIC OXIDE ACTIVITY OF THE RENAL VASCULATURE ALTERED? ANALYSIS OF A RANDOMIZED CONTROLLED TRIAL COMPARING TWO COMBINATION THERAPIES - Kannenkeril, Dennis; Ott, Christian; Bosch, Agnes; Striepe, Kristina; Pietschner, Robert; Schiffer, Mario; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Recently we demonstrated that a combination therapy with empagliflozin and linagliptin in patients with type 2 diabetes mellitus (T2DM) induce changes in renal hemodynamics. The purpose of this study was to analyze the influence of basal nitric oxide (NO) activity of the renal vasculature on the described changes of the renal hemodynamic profile. DESIGN AND METHOD: In this study patients with T2DM were nalysing to receive either empagliflozin and linagliptin (E+L group, n = 50) or metformin and insulin glargine (M+I group, n = 46), for 3 months. Renal hemodynamics were assessed with constant-infusion input-clearance technique with p-aminohippuric acid for renal plasma flow (RPF) and inulin for glomerular filtration rate (GFR) at baseline and after treatment. Due to withdrawal of inulin from the market during the study, GFR and filtration fraction (FF) were measured only in a sub-group of patients (E+L: n = 34; M+I: n = 31). Intraglomerular hemodynamics were calculated according the model established by Gomez. The basal NO activity in the renal circulation has been assessed by nalysing change in RPF in response to intravenously administrated NG-monomethyl-l-arginine (NO inhibitor). RESULTS: After 3 months of treatment, we did not observe any change in basal NO activity compared to baseline in either of the groups. In the E+L group, we found a correlation between basal NO activity of the renal vasculature after 3 months of treatment and change in RPF (r = -0.535, p < 0.001), renal blood flow (r = -0.468, p = 0.001) and renal vascular resistance (r = 0.377, p = 0.007) induced by treatment. Similar correlations with change in FF (r = 0.639, p < 0.001), preglomerular (r = 0.350, p = 0.046) and postglomerular resistance (r = 0.588, p < 0.001) have been found. No such relationships were found in the M+I group after 3 months and with basal NO activity at baseline in both treatment groups. CONCLUSIONS: Basal NO emerged as a determinant of the renal hemodynamic response in the combination therapy of empagliflozin and linagliptin, but not in the combination therapy of insulin and metformin.
CRIS-Team Scopus Importer:2022-09-09

Is GFR decline induced by SGLT2 inhibitor of clinical importance? - Günes-Altan, Merve; Bosch, Agnes; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Cardiovascular Diabetology, 2024)
Background: Use of sodium-glucose-cotransporter-2 (SGLT2) inhibitors often causes an initial decline in glomerular filtration rate (GFR). This study addresses the question whether the initial decline of renal function with SGLT2 inhibitor treatment is related to vascular changes in the systemic circulation. Methods: We measured GFR (mGFR) and estimated GFR (eGFR) in 65 patients with type 2 diabetes (T2D) at baseline and after 12 weeks of treatment randomized either to a combination of empagliflozin and linagliptin (SGLT2 inhibitor based treatment group) (n = 34) or metformin and insulin (non-SGLT2 inhibitor based treatment group) (n = 31). mGFR was measured using the gold standard clearance technique by constant infusion of inulin. In addition to blood pressure (BP), we measured pulse wave velocity (PWV) under standardized conditions reflecting vascular compliance of large arteries, as PWV is considered to be one of the most reliable vascular parameter of cardiovascular (CV) prognosis. Results: Both mGFR and eGFR decreased significantly after initiating treatment, but no correlation was found between change in mGFR and change in eGFR in either treatment group (SGLT2 inhibitor based treatment group: r=-0.148, p = 0.404; non-SGLT2 inhibitor based treatment group: r = 0.138, p = 0.460). Noticeably, change in mGFR correlated with change in PWV (r = 0.476, p = 0.005) in the SGLT2 inhibitor based treatment group only and remained significant after adjustment for the change in systolic BP and the change in heart rate (r = 0.422, p = 0.018). No such correlation was observed between the change in eGFR and the change in PWV in either treatment group. Conclusions: Our main finding is that after initiating a SGLT2 inhibitor based therapy an exaggerated decline in mGFR was related with improved vascular compliance of large arteries reflecting the pharmacologic effects of SGLT2 inhibitor in the renal and systemic vascular bed. Second, in a single patient with T2D, eGFR may not be an appropriate parameter to assess the true change of renal function after receiving SGLT2 inhibitor based therapy. Trial registration: clinicaltrials.gov (NCT02752113).
CRIS-Team Scopus Importer:2024-06-14
Keywords: GFR decline; PWV; SGLT2 inhibitors

Is vascular remodelling in patients with chronic heart failure exaggerated? - Pietschner, Robert; Bosch, Agnes; Kannenkeril, Dennis; Striepe, Kristina; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland; Kolwelter, Julie (ESC Heart Failure, 2022)
Background Vascular remodelling of large arteries increases afterload of the left ventricle. The aim of this study was to analyse whether vascular remodelling and function under laboratory and 24-hour ambulatory conditions is impaired in patients with chronic heart failure (CHF) independently of cardiovascular risk factors.
CRIS-Team WoS Importer:2022-10-21

LOW DOSE-EPLERENONE TREATMENT DECREASES AORTIC STIFFNESS IN PATIENTS WITH METABOLIC SYNDROME - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Microvascular changes at different stages of chronic kidney disease - Kannenkeril, Dennis; Frost, Shaun; Nolde, Janis M.; Kiuchi, Márcio Galindo; Carnagarin, Revathy; Lugo-Gavidia, Leslie Marisol; Chan, Justine; Joyson, Anu; Matthews, Vance B.; Herat, Lakshini Y.; Azzam, Omar; Mehdizadeh, Maryam; et al. (Journal of Clinical Hypertension, 2020)
Patients with progressing chronic kidney disease (CKD) are more likely to experience cardio- and cerebrovascular events than progressing to end-stage renal disease. The authors explored whether retinal microvascular calibers differed with the degree of renal impairment and between the standard and extended optic disk and may serve as a simple additional tool for risk stratification in this highly vulnerable patient cohort. The authors analyzed central retinal arteriolar and venular equivalent calibers (CRAE, CRVE) at different retinal zones (zone B&C) using digital retinal imaging in hypertensive patients with stage 2 (n = 66) or stage 3 CKD (n = 30). Results were adjusted for age, sex, HbA1c, and 24-hour diastolic blood pressure. Mean eGFR was 77.7 ± 8.9 and 48.8 ± 7.9 ml/min/1.73 m2 for stage 2 and 3 CKD, respectively. CRAE and CRVE in zones B and C were significantly lower in patients with stage 3 CKD compared to patients with stage 2 CKD (CRAE-B:141.1 ± 21.4 vs. 130.5 ± 18.9 µm, p =.030; CRAE-C:137.4 ± 19.4 vs 129.2 ± 18.2 µm, p =.049; CRVE-B:220.8 ± 33.0 vs. 206.0 ± 28.4 µm, p =.004; and CRVE-C:215.9 ± 33.0 vs. 201.2 ± 25.1µm, p =.003). In patients with stage 2 CKD, CRAE-B was higher than CRAE-C (141.1 ± 21.4 vs. 137.4 ± 19.4µm, p <.001). In contrast, such a difference was not found in patients with stage 3 CKD. CRAE of both retinal zones correlated with eGFR for the entire cohort. In patients with stage 3 CKD, retinal narrowing is more pronounced compared to patients with stage 2 CKD. Whether the novel observation of difference in arteriolar caliber between zones B and C in stage 2 CKD could serve as an early marker of CKD progression warrants further investigation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: chronic kidney disease; glomerular filtration rate; microvascular change; retinal vessel caliber hypertension sympathetic nervous system

Modification of Dialysate Na+ Concentration but not Ultrafiltration or Dialysis Treatment Time Affects Tissue Na+ Deposition in Patients on Hemodialysis. - Kopp, Christoph; Kittler, Lukas; Linz, Peter; Kannenkeril, Dennis; Horn, Stephan; Chazot, Charles; Schiffer, Mario; Uder, Michael; Nagel, Armin Michael; Dahlmann, Anke (Kidney International Reports, 2024)
INTRODUCTION: Tissue Na+ overload is present in patients receiving hemodialysis (HD) and is associated with cardiovascular mortality. Strategies to actively modify tissue Na+ amount in these patients by adjusting the HD regimen have not been evaluated. METHODS: In several substudies, including cross-sectional analyses (n = 75 patients on HD), a cohort study and a cross-over interventional study (n = 10 patients each), we assessed the impact of ultrafiltration (UF) volume, prolongation of dialysis treatment time, and modification of dialysate Na+ concentration on tissue Na+ content using 23Na magnetic resonance imaging (23Na-MRI). RESULTS: In the cross-sectional analysis of our patients on HD, differences in dialysate sodium concentration ([Na+]) were associated with changes in tissue Na+ content, whereas neither UF volume nor HD treatment time affected tissue Na+ amount. Skin Na+ content was lower in 17 patients on HD, with dialysate [Na+] of <138 mmol/l compared to 58 patients dialyzing at ≥138 mmol/l (20.7 ± 7.3 vs. 26.0 ± 8.8 arbitrary units [a.u.], P < 0.05). In the cohort study, intraindividual prolongation of HD treatment time was not associated with a reduction in tissue Na+ content. Corresponding to the observational data, intraindividual modification of dialysate [Na+] from 138 to 142 to 135 mmol/l resulted in concordant changes in skin Na+ (24.3 ± 7.6 vs. 26.3 ± 8.0 vs. 20.8 ± 5.6 a.u, P < 0.05 each), whereas no significant change in muscle Na+ occurred. CONCLUSION: Solely adjustment of dialysate [Na+] had a reproducible impact on tissue Na+ content. 23Na-MRI could be utilized to monitor the effectiveness of dialysate [Na+] modifications in randomized-controlled outcome trials.
EVALuna2:568181

PCSK-9-inhibitor therapy improves endothelial function in high-risk patients with cardiovascular disease - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Pietschner, Robert; Ott, Christian; Schiffer, Mario; Achenbach, Susanne; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

PCSK-9-inhibitor therapy improves endothelial function in high-risk patients with cardiovascular disease - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Berner, Laura; Pietschner, Robert; Ott, Christian; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Clinical Research in Cardiology, 2024)
Background: Impaired endothelial function predicts cardiovascular events. The aim of this study was to analyze the effect of evolocumab on endothelial function in patients with cardiovascular disease. Methods: This was a prospective, double-blinded, randomized, controlled, single center study including patients with cardiovascular disease and treated with statins. Patients were consecutively randomized (1:1) to either evolocumab treatment or placebo. All patients underwent examination of endothelial function at baseline, and after 1, 4 and 8 weeks of treatment by a semi-automatic high-resolution ultrasound system (UNEX EF 18G). Parameters of endothelial function were flow-mediated vasodilation (FMD), low flow-mediated vasoconstriction (L-FMC) and vasoactive range (VAR). Results: Hundred three patients with a mean age of 66.2 ± 7.7 years and a mean LDL-cholesterol of 98 ± 19.1 mg/dl completed the study. The change in VAR from baseline to week 8 was significantly different with evolocumab compared to placebo (p = 0.045). Moreover, VAR increased after 8 weeks of treatment with evolocumab compared to baseline (p = 0.034). No change has been noticed in FMD and L-FMC after 8 weeks of treatment with evolocumab. In subgroup analyses, VAR improved in patients with age ≤ 67 years, lower systolic blood pressure (≤ 125 mmHg) and higher baseline LDL-cholesterol (> 95 mg/dl), (p = 0.006, p = 0.049 and p = 0.042, respectively) after 8 weeks of evolocumab treatment. No serious adverse event related to study medication occurred during the study. Conclusion: Our data indicate that endothelial function improved with evolocumab treatment in high-risk patients on statin therapy with preexisting cardiovascular disease. Our results contribute to the mechanistic explanation why lower incidence of the cardiovascular composite endpoint has been demonstrated in the FOURIER study. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-11-29
Keywords: Endothelial function; Evolocumab; Flow-mediated vasodilation; PCSK-9 inhibitor; Vasoactive range

Pleiotropic effects under combined therapy with empagliflozin and linagliptin compared to metformin and insulin glargine in patients with type 2 diabetes - Jung, Susan; Ott, Christian; Kannenkeril, Dennis; Bosch, Agnes; Karg, M.; Striepe, Kristina; Bramlage, P.; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Predicting blood pressure response to renal denervation based on a new approach - Bytyqi, Venera; Kannenkeril, Dennis; Striepe, Kristina; Bosch, Agnes; Karg, Marina V.; Schmid, Axel; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2024)
Background: Identifying predictors of blood pressure (BP) response to renal denervation (RDN) is crucial for patient selection. According to Wilder's principle, baseline BP predicts BP change after any antihypertensive intervention. Thus, any observed BP change after RDN is the sum of the BP change depending on the baseline BP and the specific BP reduction due to RDN. Based on this concept, we propose a new definition of BP responders. Methods: In our center, 148 patients with uncontrolled hypertension underwent RDN, and 24-h ambulatory BP (ABP) was measured at baseline, and 6 months after the procedure. The decrease in 24-h systolic BP (SBP) correlated with baseline SBP (P = <0.001, r = -0.374). We determined the RDN-specific effect by subtracting the predicted SBP decrease from the observed SBP decrease. The cohort was divided into RDN responders, neutral responders, and nonresponders. Results: Our study population had a mean age of 59 ± 10.4 years and was 74% male. The RDN-specific (residual) 24-h ABP decreased by -14.9 ± 6.3/-8.2 ± 3.8 mmHg (responder group), 1.0 ± 3.2/0.2 ± 1.9 mmHg (neutral group), and 14.2 ± 10.4/8.3 ± 3.9 mmHg (nonresponder group) 6 months after RDN. Responders had fewer antihypertensive medications (P = 0.018), higher baseline office heart rate (HR) (P = 0.019), higher 24-h ambulatory HR (P = 0.003), lower BMI (P < 0.038), and absence of type 2 diabetes (T2D) (P = 0.020). Conclusion: Our definition of BP responders to RDN separates baseline BP-related changes from RDN-specific changes. Positive predictors for BP response to RDN include low BMI, fewer antihypertensive medications, high baseline office HR, high 24-h ambulatory HR, and absence of T2D.
CRIS-Team Scopus Importer:2024-11-29
Keywords: clinical predictors; renal denervation; renal denervation responders

Reduced tissue sodium content is related to improvement of vascular function in patients with chronic heart failure treated with the SGLT2 inhibitor empagliflozin - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, P.; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Reduction of tissue sodium content by SGLT-2-inhibition with dapagliflozin - Karg, M. V.; Ott, Christian; Linz, Peter; Jumar, A.; Kannenkeril, Dennis; Titze, J.; Hammon, Matthias; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36268

RELATION BETWEEN NOISE ANNOYANCE, STRESS HORMONES AND THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Rauh, Manfred; Ott, Christian; Striepe, Kristina; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Relation between waist circumference and the renal hemodynamic in healthy individuals - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Nutrition Metabolism and Cardiovascular Diseases, 2024)
Background and aims: Obesity has been shown to be an independent risk factor for the development of CKD. Little is known about pathways of interaction of visceral fat mass estimated by waist circumference (WC) and metabolic factors with the renal and intraglomerular hemodynamic profile in healthy, non-obese individuals. Methods and results: The study population of this post-hoc analysis in 80 healthy individuals, who participated in a randomized, controlled clinical trial (www.clinicaltrials.gov: NCT02783456) was divided into two groups based on median of WC (high WC and low WC group). Renal hemodynamic profiles were analyzed using steady state input clearance (infusion of para-amino-hippuric acid and inulin). Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated (Gomez equation). The analysis included healthy, non-smoking individuals, aged 27 ± 9 years with median WC of 84.75 ± 9 cm. Glomerular filtration rate (GFR) (110 ± 15 vs. 127 ± 16 ml/min/m2, p < 0.001), renal plasma flow (RPF) (620 ± 109 vs. 700 ± 104 ml/min, p = 0.001) and IGP (36.7 ± 2.3 vs. 38.5 ± 3.1 mmHg, p = 0.003) were lower in the high WC compared to the low WC group. Patients in the high WC group showed higher renal vascular resistance (RVR) (85 ± 19 vs. 70 ± 12 mmHg/(ml/min), p < 0.001), higher RA (4034 ± 1177 vs. 3069 ± 786 dyn∗s/cm5, p < 0.001) and higher RE (2283 ± 339 vs. 2118 ± 280 dyn∗s/cm5, p = 0.021) compared to the low WC group. Individuals in the high WC group showed higher leptin levels (p = 0.003) and higher HOMA-IR (p = 0.024) compared to the low WC group. Conclusion: Increased WC in healthy young individuals was associated with reduced GFR and RPF likely mediated by increased RVR.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Clearance analysis; Obesity; Renal hemodynamic; Waist circumference

Renal adaptation in pre-obesity patients with hypertension - Bosch, Agnes; Rauh, Manfred; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Journal of Hypertension, 2024)
Background and hypothesis: Obesity aggravates the risk to develop chronic kidney disease in hypertensive patients. Whether pre-obesity already impairs renal function, renal perfusion and intraglomerular hemodynamics in hypertensive patients is unknown. Methods: Renal hemodynamic profiles were measured using steady state input clearance (infusion of para-amino-hippuric acid and inulin) in 36 patients with primary arterial hypertension stage 1-2 without antihypertensive medication. Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated. The study population was divided into two groups based on median of waist circumference (WC) (96 cm) (pre-obesity and non-obesity group1) and median of body mass index (BMI) (26.5 kg/m2) (pre-obesity and non-obesity group2), respectively. Results: All patients were males, non-smoking, aged 36 ± 10 years, with an office blood pressure of 145 ± 8.6/89 ± 11.8 mmHg. None of the patients had cardiovascular disease. Patients from the pre-obese group 1 showed lower glomerular filtration rate (GFR), lower renal plasma flow (RPF) and lower IGP compared to the non-obese group1. Renal vascular resistance (RVR) and RA were higher in the pre-obese group1 compared to the non-obese group1. Similar differences in the hemodynamic profile were found for patients in the pre-obesity group2 compared to the non-obesity group2. Conclusion: The renal hemodynamic profile in hypertensive patients with pre-obesity, irrespective whether defined by WC or BMI, was characterized by a reduced GFR and RPF and by an increased RVR preferentially at the preglomerular site. Our results suggest that hypofiltration is the first phase of renal adaptation in pre-obesity hypertension.
CRIS-Team Scopus Importer:2024-09-20
Keywords: body mass index; clearance analysis; pre-obesity; renal hemodynamic; waist circumference

Renal and intraglomerular haemodynamics in chronic heart failure with preserved and reduced ejection fraction - Jung, Susanne; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Schuster, Tizia; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Congestive heart failure (CHF) and impaired renal function are two often co-existing medical conditions and associated with adverse cardiovascular outcome. The aim of the current study was to assess renal and intraglomerular haemodynamics by constant infusion input clearance technique in subjects with CHF. Methods and results: The group of subjects with CHF consisted of 27 individuals with HFpEF and 27 individuals with HFrEF and were compared with 31 healthy controls. Subjects underwent renal clearance examination to measure glomerular filtration rate (GFR) and renal blood and plasma flow (RBF and RPF) and to calculate intraglomerular haemodynamics such as resistances of the afferent (RA) and efferent arterioles (RE) as well as intraglomerular pressure (Pglom). Measured GFR was lower in CHF subjects (68.1 ± 10.1 mL/min/1.73 m2) compared with controls (83.6 ± 13.4 mL/min/1.73 m2, Padj < 0.001) as was Pglom (Padj < 0.001). Total renal vascular resistance (RVR) was higher in CHF subjects (87.3 ± 20.1 vs. 73.8 ± 17.1 dyn × s/cm5, Padj < 0.001) mediated by an increased resistance at the afferent site (3201 ± 1084 vs. 2181 ± 796 dyn × s/cm5, Padj < 0.001). Comparing HFpEF and HFrEF subjects, RA was higher in HFrEF subjects. The severity of CHF assessed by NT-proBNP revealed an inverse association with renal perfusion (RPF r = −0.421, P = 0.002, RBF r = −0.414, P = 0.002) and a positive relation with RVR (r = 0.346, P = 0.012) at the post-glomerular site (RE: r = 0.318, P = 0.022). Conclusions: Renal function assessed by measured GFR is reduced and renal vascular resistance at the preglomerular, afferent site is increased in HFpEF and, to greater extent, in HFrEF. Our data indicate a close cardiorenal interaction in CHF.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Cardiorenal interaction; Heart failure; Preserved ejection fraction; Reduced ejection fraction; Renal haemodynamics

Renal hemodynamic effects differ between antidiabetic combination strategies: randomized controlled clinical trial comparing empagliflozin/linagliptin with metformin/insulin glargine - Ott, Christian; Jung, Susanne; Korn, Manuel; Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Type 2 diabetes causes cardio-renal complications and is treated with different combination therapies. The renal hemodynamics profile of such combination therapies has not been evaluated in detail. Methods: Patients (N = 97) with type 2 diabetes were randomized to receive either empagliflozin and linagliptin (E+L group) or metformin and insulin glargine (M+I group) for 3 months. Renal hemodynamics were assessed with para-aminohippuric acid and inulin for renal plasma flow (RPF) and glomerular filtration rate (GFR). Intraglomerular hemodynamics were calculated according the Gomez´ model. Results: Treatment with E+L reduced GFR (p = 0.003), but RPF remained unchanged (p = 0.536). In contrast, M+I not only reduced GFR (p = 0.001), but also resulted in a significant reduction of RPF (p < 0.001). Renal vascular resistance (RVR) decreased with E+L treatment (p = 0.001) but increased with M+I treatment (p = 0.001). The changes in RPF and RVR were different between the two groups (both padjust < 0.001). Analysis of intraglomerular hemodynamics revealed that E+L did not change resistance of afferent arteriole (RA) (p = 0.116), but diminished resistance of efferent arterioles (RE) (p = 0.001). In M+I group RA was increased (p = 0.006) and RE remained unchanged (p = 0.538). The effects on RA (padjust < 0.05) and on RE (padjust < 0.05) differed between the groups. Conclusions: In patients with type 2 diabetes and preserved renal function treatment with M+I resulted in reduction of renal perfusion and increase in vascular resistance, in contrast to treatment with E+I that preserved renal perfusion and reduced vascular resistance. Moreover, different underlying effects on the resistance vessels have been estimated according to the Gomez model, with M+I increasing RA and E+L predominantly decreasing RE, which is in contrast to the proposed sodium-glucose cotransporter 2 inhibitor effects. Trial registration: The study was registered at www.clinicaltrials.gov (NCT02752113) on April 26, 2016
CRIS-Team Scopus Importer:2021-09-17
Keywords: Hemodynamics; Intraglomerular; Renal; Type 2 diabetes

Response of Blood Pressure to Renal Denervation Is Not Associated with Genetic Variants - Delles, Christian; Schmieder, Roland; Daly, Rónán; Kannenkeril, Dennis; Bosch, Agnes; Lauder, Lucas; Kunz, Michael; Böhm, Michael; Hamilton, Graham; Schmieder, Raphael; Schmid, Axel; Herzyk, Pawel; et al. (Hypertension, 2024)
BACKGROUND: Renal denervation lowers blood pressure (BP) in patients with uncontrolled hypertension. We conducted an unbiased genomic screen to identify genetic variants that may associate with BP response to renal denervation (RDN). METHODS: Patients (n=268) with uncontrolled resistant hypertension (baseline BP, 166±21/90±15 mm Hg) who underwent endovascular RDN using the Symplicity catheter (Medtronic, Inc, Santa Rosa, CA) were included. Reduction in 24-hour ambulatory systolic BP was assessed at 6 months and divided into 2 groups: above and below the median response of 6.0 mm Hg, taking preintervention 24-hour ambulatory BP and regression to the mean into account. Whole exome sequencing assessing 249 669 variants, was conducted using Illumina NovaSeq technology read on a NovaSeq S4 Flow Cell device. RESULTS: We did not identify individual gene variants associated with BP response following RDN. These findings were confirmed after adjustment for sex and in a sensitivity analysis looking at tertiles of BP response. We also explored specific variants in AGT, ADD1, ADRB1, ADRB2, and SCNN1A that have been proposed as potential candidate genes for response and found no association (all P>0.13). Gene ontology analysis of variants across the 2 responder groups highlighted differences in biologic processes such as cell adhesion and molecular function such as protein tyrosine kinase activity. CONCLUSIONS: The response to RDN, in terms of 24-hour BP reduction, was not associated with the genetic profile of patients with resistant hypertension. These data do not support the use of a genetic score to identify potential responders to RDN.
CRIS-Team Scopus Importer:2024-12-06
Keywords: blood pressure; catheters; genetic profile; genomics; hypertension

Retinal Capillary Damage Is Already Evident in Patients With Hypertension and Prediabetes and Associated With HbA1c Levels in the Nondiabetic Range. - Kannenkeril, Dennis; Nolde, Janis M.; Kiuchi, Márcio Galindo; Carnagarin, Revathy; Lugo-Gavidia, Leslie Marisol; Chan, Justine; Joyson, Anu; Jose, Ancy; Robinson, Sandi; Matthews, Vance B.; Herat, Lakshini Y.; Azzam, Omar; et al. (Diabetes Care, 2022)
OBJECTIVE: We analyzed whether any change in capillary density in the retinal circulation could be detected in patients with hypertension in the prediabetic stage. RESEARCH DESIGN AND METHODS: In a cross-sectional analysis, we assessed capillary density in the foveal (CDF) and parafoveal retinal areas using optical coherence tomography-angiography in 62 patients with hypertension and normal glucose metabolism and 40 patients with hypertension and prediabetes. RESULTS: The CDF was lower in patients with prediabetes than in those with normal glucose metabolism. Moreover, we found a correlation between CDF and HbA1c and glucose levels for the entire cohort. In patients with HbA1c <6.5% (48 mmol/mol), CDF was lower in patients with HOMA for insulin resistance (HOMA-IR) ≥2.5 than in patients with HOMA-IR <2.5. CONCLUSIONS: Patients with hypertension and prediabetes display retinal capillary changes, and an association with markers of glucose metabolism exists, even within a nondiabetic HbA1c range.
EVALuna2:505649

Retinal neurodegeneration in patients with end-stage renal disease assessed by spectral-domain optical coherence tomography - Jung, Susanne; Bosch, Agnes; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Scientific Reports, 2020)
Spectral-domain optical coherence tomography (SD-OCT) represents a reliable tool for retinal layer volume and thickness measurement. The aim of this study was to evaluate retinal changes indicating neurodegenerative processes in patients with end-stage renal disease (ESRD) compared to healthy controls. This was a cross-sectional, single-center study comprising 32 ESRD patients and 38 controls. Sectoral retinal nerve fiber layer (RNFL) thickness and retinal layer volumes were obtained by SD-OCT. Age- and gender-adjusted retinal layer volumes such as total retinal volume (p = 0.037), ganglion cell layer volume (GCL, p = 0.003), ganglion cell layer – inner plexiform layer volume (GCL-IPL, p = 0.005) and inner retinal layer volume (IRL, p = 0.042) of the right eye were lower in ESRD patients. Inner plexiform layer volume of both eyes (IPL, right eye: p = 0.017; left eye: 0.044) was reduced, as was RNFL thickness in the temporal superior sector (right eye: p = 0.016). A subgroup analysis excluding patients with diabetes revealed that GCL (p = 0.014) and GCL-IPL volume of the right eye (p = 0.024) and temporal superior sector of the RNFL scan (p = 0.021) in ESRD patients were still significantly thinner. We observed a decrease in several retinal layer volumes and temporal RNFL thickness indicative of retinal neurodegenerative processes in patients with ESRD.
CRIS-Team Scopus Importer:2020-04-03

Retinal vascular resistance in arterial hypertension - Kannenkeril, Dennis; Harazny, Joanna M.; Bosch, Agnes; Ott, Christian; Michelson, Georg; Schmieder, Roland; Friedrich, Stefanie (Blood Pressure, 2017)
Retinal microcirculation represents an easily accessible, non-invasive, in-vivo possibility to assess early microvascular changes. In addition to the assessment of functional (e.g. retinal capillary flow, RCF) and retinal arteriolar structural parameters (e.g. wall-to-lumen-ratio, WLR) we now suggest a new parameter reflecting the resistance in small retinal arterioles (RVR).In 45 normotensive (NT) subjects and 123 patients with hypertension stage 1 (HT) we assessed RCF, WLR, arteriolar diameter, lumen diameter and wall cross section area in the retinal circulation by using scanning laser Doppler flowmetry (SLDF). Mean arterial pressure (MAP) was measured immediately before the SLDF measurement and retinal vascular resistance was calculated (RVR = MAP/RCF). In a separate study the test-retest reliability was determined in 6 volunteers from our clinical staff by assessing RVR three times within six weeks.The analysis of the volunteers revealed a coefficient of variation for RVR of 7.75 ± 2.11% and Cronbach´s alpha was 0.90. WLR, a marker of vascular remodeling did not differ between NT and HT. In contrast, RCF and inner diameter of the retinal arterioles (ID) were significantly lower (RCF: p = .045 and ID: p = .001) in the HT group than in the NT group and RVR was significantly higher in the HT group than in the NT group (p < .001). In both groups we found no correlation of RVR with age, but a significant correlation of RVR with WLR (NT: r = 0.34, p = .006; HT: r = 0.25, p = .01), indicating that the RVR reflects vascular remodeling in the retinal circulation.Our data showed an increased retinal vascular resistance in hypertensive patients compared to non-hypertensive patients prior to the occurrence of structural retinal vascular remodeling. The correlation between RVR and WLR indicates that RVR is a reliable, non-invasive and early-sensitive marker of vascular remodeling in early hypertension.
EVALuna2:4030

Role of Microparticles in Cardiovascular Disease Implications for Endothelial Dysfunction, Thrombosis, and Inflammation - Lugo-Gavidia, Leslie Marisol; Burger, Dylan; Matthews, Vance B.; Nolde, Janis M.; Galindo Kiuchi, Marcio; Carnagarin, Revathy; Kannenkeril, Dennis; Chan, Justine; Joyson, Anu; Herat, Lakshini Y.; Azzam, Omar; Schlaich, Markus P. (Hypertension, 2021)
Microparticles are small cell vesicles that are derived from the cell membrane in response to different biological processes. There is growing evidence supporting the association between microparticles and cardiovascular disease, as their pathophysiology commonly includes endothelial damage and chronic inflammation which also promote a prothrombotic state. The direct causal link between the release of the different subtypes of microparticles and their implications on physiological and pathological conditions is still not completely elucidated. However, evidence suggests microparticles released from platelets, leukocytes, and endothelium may help to evaluate vascular health as they have a relevant role in inflammation, endothelial function, and thrombosis. This review aims to provide a short overview of the biogenesis, characteristics, and detection methodology of microparticles with a special focus on their possible implication in cardiovascular settings.
CRIS-Team WoS Importer:2021-06-11

SEMI-AUTOMATIC MEASUREMENT OF INTIMA-MEDIA THICKNESS OF BRACHIAL ARTERY IN PATIENTS WITH CONGESTIVE HEART FAILURE - Kannenkeril, Dennis; Kolwelter, Julie; Pietschner, Robert; Striepe, Kristina; Bosch, Agnes; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

SEMI-AUTOMATIC MEASUREMENT OF INTIMA-MEDIA THICKNESS OF BRACHIAL ARTERY IN PATIENTS WITH CONGESTIVE HEART FAILURE - Kannenkeril, Dennis; Kolwelter, Julie; Pietschner, Robert; Striepe, Kristina; Bosch, Agnes; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Cardiovascular diseases are associated with an increase in intima-media thickness (IMT). However, the techniques used to measure IMT have limitations. A semi-automatic device called UNEX has been developed, which overcomes the limitation of classic systems (in particular the investigator-dependency of conventional, "hand-held'' measurements). The purpose of this study was to measure the intima-media thickness of the brachial artery (bIMT) with the UNEX device in patients with and without congestive heart failure. DESIGN AND METHOD: The UNEX device is comprised of a 7.5-MHz, H-shaped linear array transducer and a novel stereotactic probe-holding device (UNEX EF 18G; UNEX Co., Nagoya, Japan). Another advantage of this device is the continuous recording of B-mode images and A-mode waves of the brachial artery. Measurement of bIMT was automatically performed on A-mode images of the far wall of the brachial artery. The analysis system automatically detects the measurement point where an image was clearly obtained. The average of mean measurement values obtained from 10 cardiac cycles was defined as bIMT. In a first set of clinical studies, we measured bIMT in patients with reduced left ventricular ejection fraction (HFrEF) and in patients without heart failure. RESULTS: Patients with HFrEF (n = 85, ejection fraction: 38.3 ± 8.4 %, NT-pro-BNP: 713 ± 714.7 pg/ml) compared to patients without heart failure (n = 63) were older (66.4 ± 9.2 vs. 53.8 ± 12.6 years, p < 0.001), with more male subjects (67 vs. 40, p = 0.039). bIMT was higher in patients with HFrEF compared to the other group (0.295 ± 0.083 vs. 0.249 ± 0.083 mm, p < 0.001). After adjustment for age, gender and other cardiovascular risk factors, the result remained significant (p = 0.032). CONCLUSIONS: Our study demonstrate that IMT of large muscular arteries can be automatically (investigator independently) measured. Our data indicate an increased vascular remodeling in patients with HFrEF independent of other confounders.
CRIS-Team Scopus Importer:2022-09-16

SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial - Karg, Margarete; Bosch, A.; Kannenkeril, Dennis; Striepe, Kristina; Ott, Christian; Schneider, M. P.; Boemke-Zelch, Franziska; Linz, Peter; Nagel, Armin Michael; Titze, Jens; Uder, Michael; Schmieder, Roland (Cardiovascular Diabetology, 2018)
Sodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.In a prospective double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to either dapagliflozin 10 mg or placebo once daily for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analysed the sodium content in the skin and muscles of the lower leg by Na-MRI.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11 mmHg, p = 0.010), and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024), 24-h ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline [24.1 ± 6.6 vs. 22.7 ± 6.4 A.U.(arbitrary unit) p = 0.013]. No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 A.U. p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in tissue sodium content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT02383238) retrospectively registered.
EVALuna2:4043

Simultaneously measured interarm blood pressure difference is not associated with pulse wave velocity in a clinical dataset of at-risk hypertensive patients - Nolde, J.; Lugo-Gavidia, L. M.; Kannenkeril, Dennis; Chan, J.; Robinson, Sandi; Jose, A.; Joyson, A.; Schlaich, L.; Carnagarin, Revathy; Azzam, O.; Kiuchi, M.; Schlaich, Markus (European Heart Journal, 2021)
Abstract Background/Introduction Recent analysis of systolic inter-arm differences in blood pressure from the INTERPRESS-IPD Collaboration suggest an association with increased all-cause mortality, cardiovascular mortality and cardiovascular events, previous studies have demonstrated associations with other risk parameters. Purpose We aimed to reproduce these associations in a cohort of 199 treated, at-risk, hypertensive patients with pulse wave velocity (PWV) as a surrogate marker of cardiovascular (CV) damage. Methods Simultaneously measured Inter-arm blood pressure differences, 24 hour ambulatory BP and PWV were measured in 199 treated patients of a tertiary hospital hypertension outpatient clinic. Associations between systolic inter-arm BP difference and PWV were analyzed with uni- and multivariate regression models. Results Out of 199 participants, 90 showed an Inter-arm blood pressure difference of more than 5 mmHg. The Inter-arm difference was not associated with PWV. Furthermore, neither observed single blood pressure measurements nor 24 hour ambulatory blood pressure was associated with Inter-arm blood pressure differences. Conclusion In our clinical patient cohort we failed to observe an association between inter-arm BP differences and PWV. Mode of assessment, study design or the sample characteristics of this treated, hypertensive cohort may explain the negative results. The limited sample size of the study poses a challenge to the detection of smaller effects in our study.
CRIS-Team WoS Importer:2021-12-10
Keywords: Target Organ Damage; Left Ventricular Hypertrophy

Simultaneously measured inter-arm blood pressure difference is not associated with pulse wave velocity in a clinical dataset of at-risk hypertensive patients - Nolde, Janis M.; Lugo-Gavidia, Leslie Marisol; Kannenkeril, Dennis; Chan, Justine; Robinson, Sandi; Jose, Ancy; Joyson, Anu; Schlaich, Luca; Carnagarin, Revathy; Azzam, Omar; Kiuchi, Márcio Galindo; Schlaich, Markus P. (Journal of Human Hypertension, 2021)
Recent analysis of systolic inter-arm differences in blood pressure from the INTERPRESS-IPD Collaboration suggest an association with increased all-cause mortality, cardiovascular mortality and cardiovascular events. Previous studies have demonstrated associations with other risk parameters. We aimed to reproduce these associations in a cohort of 199 treated, at-risk hypertensive patients with pulse wave velocity (PWV) as a surrogate marker of cardiovascular (CV) damage. Simultaneously measured inter-arm blood pressure (BP) differences, 24 hour ambulatory BP and PWV were measured in 199 treated patients from a tertiary hospital hypertension outpatient clinic. Associations between systolic inter-arm BP difference and PWV were analyzed with uni- and multi-variate regression models. Out of 199 participants, 90 showed an inter-arm BP difference of more than 5 mmHg. The inter-arm difference was not associated with PWV. Furthermore, neither observed single BP measurements nor 24 hour ambulatory BP was associated with inter-arm BP differences. In our clinical patient cohort we failed to observe an association between inter-arm BP differences and PWV. Mode of assessment, study design and the sample characteristics of this treated, hypertensive cohort may have contributed to the negative findings. The limited sample size of the study poses a challenge to the detection of smaller effects in our study.
CRIS-Team Scopus Importer:2021-08-13

Skin sodium content as a predictor of blood pressure response to renal denervation - Günes-Altan, Merve; Schmid, Axel; Kannenkeril, Dennis; Linz, Peter; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Hypertension Research, 2023)
Patients with treatment resistant hypertension (TRH) are known to have elevated sodium (Na) content in muscle and skin. Renal denervation (RDN) emerged as an adjacent therapeutic option in this group of patients. This analysis aimed at evaluating whether tissue Na content predicts blood pressure (BP) response after RDN in patients with TRH. Radiofrequency-device based RDN was performed in 58 patients with uncontrolled TRH. Office and 24-h ambulatory BP were measured at baseline and after 6 months. To assess tissue Na content Na magnetic resonance imaging (Na-MRI) was performed at baseline prior to RDN. We splitted the study cohort into responders and non-responders based on the median of systolic 24-h ambulatory blood pressure (ABP) reduction after 6 months and evaluated the association between BP response to RDN and tissue Na content in skin and muscle. The study was registered at http://www.clinicaltrials.gov (NCT01687725). Six months after RDN 24-h ABP decreased by −8.6/−4.7 mmHg. BP-Responders were characterized by the following parameters: low tissue sodium content in the skin (p = 0.040), female gender (p = 0.027), intake of aldosterone antagonists (p = 0.032), high baseline 24-h night-time heart rate (p = 0.045) and high LDL cholesterol (p < 0.001). These results remained significant after adjustment for baseline 24-h systolic BP. Similar results were obtained when the median of day-time and night-time ABP reduction after 6 months were used as cut-off criteria for defining BP response to RDN. We conclude that in addition to clinical factors including baseline 24-h ABP Na-MRI may assist to select patients with uncontrolled TRH for RDN treatment. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-11-03
Keywords: Renal denervation; Sodium MRI; Tissue sodium

Sodium quantification in skeletal muscle: comparison between Cartesian gradient-echo and radial ultra-short echo time 23Na MRI techniques - Gerhalter, Teresa; Schilling, Felix; Zeitouni, Nour; Linz, Peter; Baudin, Pierre Yves; Kannenkeril, Dennis; Kopp, Christoph; Dahlmann, Anke; Schmieder, Roland; Uder, Michael; Nagel, Armin Michael; Gast, Lena (European Radiology Experimental, 2024)
Background: Clinical magnetic resonance imaging (MRI) studies often use Cartesian gradient-echo (GRE) sequences with 2-ms echo times (TEs) to monitor apparent total sodium concentration (aTSC). We compared Cartesian GRE and ultra-short echo time three-dimensional (3D) radial-readout sequences for measuring skeletal muscle aTSC. Methods: We retrospectively evaluated 211 datasets from 112 volunteers aged 62.3 ± 12.1 years (mean ± standard deviation), acquired at 3 T from the lower leg. For 23Na MRI acquisitions, we used a two-dimensional Cartesian GRE sequence and a density-adapted 3D radial readout sequence with cuboid field-of-view (DA-3D-RAD-C). We calibrated the 23Na MR signal using reference tubes either with or without agarose and subsequently performed a relaxation correction. Additionally, we employed a six-echo 1H GRE sequence and a multi-echo spin-echo sequence to calculate proton density fat fraction (PDFF) and water T2. Paired Wilcoxon signed-rank test, Cohen dz for paired samples, and Spearman correlation were used. Results: Relaxation correction effectively reduced the differences in muscle aTSC between the two acquisition and calibration methods (DA-3D-RAD-C using NaCl/agarose references: 20.05 versus 19.14 mM; dz = 0.395; Cartesian GRE using NaCl/agarose references: 19.50 versus 18.82 mM; dz = 0.427). Both aTSC of the DA-3D-RAD-C and Cartesian GRE acquisitions showed a small but significant correlation with PDFF as well as with water T2. Conclusions: Different 23Na MRI acquisition and calibration approaches affect aTSC values. Applying relaxation correction is advised to minimize the impact of sequence parameters on quantification, and considering additional fat correction is advisable for patients with increased fat fractions. Relevance statement: This study highlights relaxation correction’s role in improving sodium MRI accuracy, paving the way for better disease assessment and comparability of measured sodium signal in patients. Key points: • Differences in MRI acquisition methods hamper the comparability of sodium MRI measurements. • Measured sodium values depend on used MRI sequences and calibration method. • Relaxation correction during postprocessing mitigates these discrepancies. • Thus, relaxation correction enhances accuracy of sodium MRI, aiding its clinical use. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calibration; Magnetic resonance imaging; Muscle (skeletal); Sodium; Volunteers

Supine blood pressure—A clinically relevant determinant of vascular target organ damage in hypertensive patients - Nolde, Janis M.; Kiuchi, Márcio Galindo; Carnagarin, Revathy; Frost, Shaun; Kannenkeril, Dennis; Lugo-Gavidia, Leslie Marisol; Chan, Justine; Joyson, Anu; Matthews, Vance B.; Herat, Lakshini Y.; Azzam, Omar; Schlaich, Markus P. (Journal of Clinical Hypertension, 2020)
Night-time blood pressure (BP) is an important predictor of cardiovascular outcomes. Its assessment, however, remains challenging due to limited accessibility to ambulatory BP devices in many settings, costs, and other factors. We hypothesized that BP measured in a supine position during daytime may perform similarly to night-time BP when modeling their association with vascular hypertension-mediated organ damage (HMOD). Data from 165 hypertensive patients were used who as part of their routine clinic workup had a series of standardized BP measurements including seated attended office, seated and supine unattended office, and ambulatory BP monitoring. HMOD was determined by assessment of kidney function and pulse wave velocity. Correlation analysis was carried out, and univariate and multivariate models were fitted to assess the extent of shared variance between the BP modalities and their individual and shared contribution to HMOD variables. Of all standard non-24-hour systolic BP assessments, supine systolic BP shared the highest degree of variance with systolic night-time BP. In univariate analysis, both systolic supine and night-time BP were strong determinants of HMOD variables. In multivariate models, supine BP outperformed night-time BP as the most significant determinant of HMOD. These findings indicate that supine BP may not only be a clinically useful surrogate for night-time BP when ambulatory BP monitoring is not available, but also highlights the possibility that unattended supine BP may be more closely related to HMOD than other BP measurement modalities, a proposition that requires further investigations in prospective studies.
CRIS-Team Scopus Importer:2020-12-11
Keywords: hypertension-mediated organ damage; kidney function; nocturnal blood pressure; pulse wave velocity; supine blood pressure

The influence of aircraft noise exposure on the systemic and renal haemodynamics - Bosch, Agnes; Kannenkeril, Dennis; Jung, Susanne; Striepe, Kristina; Karg, Marina V.; Ott, Christian; Schmieder, Roland (European Journal of Preventive Cardiology, 2022)
Aims: Epidemiological studies found a link between aircraft noise exposure and increased incidence of arterial hypertension and cardiovascular disease, but the underlying pathophysiological mechanisms are not fully understood. Clinical studies have shown that mental stress affects the systemic and renal haemodynamic, but no such study was performed with noise exposure as stress factor. We analysed systemic and renal effects of 25 min standardized aircraft noise in a sham controlled clinical study including 80 healthy men and 34 male patients with hypertension. Methods and results: Systemic haemodynamic parameters were measured using electrocardiography and impedance cardiography. The renal haemodynamic was assessed using steady state input clearance with infusion of para-aminohippuric acid and inulin for glomerular filtration rate and renal plasma flow, respectively. In the systemic circulation of hypertensive patients, there was an increase in total peripheral resistance (TPR) (1420 ± 387 vs. 1640 ± 516 dyn·s·cm-5, P = 0.001) and a decrease in cardiac index (CI) (2.9 ± 0.8 vs. 2.6 ± 0.8 L/(min·m2, P < 0.001) 25 min after the start of noise exposure, which was not present during sham procedure (P = 0.10, P = 0.86). In healthy individuals a procedure induced increase in TPR and decrease in CI was present after noise (TPR: 995 ± 239 vs. 1106 ± 308 dyn·s·cm-5, P = 0.001, CI: 3.6 ± 0.7 vs. 3.3 ± 0.9 L/(min·m2, P < 0.001) and sham application (TPR: P = 0.002, CI: P < 0.001). However, in healthy individuals changes in TPR (P = 0.450) and CI (P = 0.605) from baseline until 25 min after the start of the intervention did not differ between noise and sham exposure. In the renal circulation of hypertensive patients and healthy individuals the response did not differ between noise and sham procedure. Conclusions: In hypertensive but not healthy men we observed a systemic vasoconstrictive response after aircraft noise exposure accompanied by a decrease in CI. No significant changes were observed in the renal circulation. Our results suggest that male hypertensive patients are more susceptible for noise-induced changes of vascular resistance in the systemic circulation.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Aircraft noise; Clearance; Hypertension; Renal haemodynamic; Systemic haemodynamic

THE INFLUENCE OF ANNOYANCE DUE TO AIRCRAFT NOISE ON RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Harazny, J. M.; Striepe, Kristina; Karg, M. V.; Jung, Susan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

THE INFLUENCE OF ANNOYANCE DUE TO NOISE ON RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, C.; Harazny, J. M.; Striepe, Kristina; Karg, M.; Dienemann, T.; Jung, Susan; Schmieder, Roland (2018)
EVALuna2:202962

THE SGLT2 INHIBITOR EMPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content

Tissue sodium concentration correlates with hypertrophic vascular remodelling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susan; Harazny, Jeremy; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Tissue sodium concentration emerged as a determinant of hypertrophic vascular remodeling in type 2 diabetes - Schmieder, Roland; Jung, Susanne; Kannenkeril, Dennis; Harazny, J. M.; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Angela; Uder, Michael (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Tissue sodium content in patients with type 2 diabetes mellitus - Kannenkeril, Dennis; Karg, Marina V.; Bosch, Agnes; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2019)
Background: Tissue sodium content by 23 Na magnetic resonance imaging (MRI)has been found to be increased in arterial hypertension. We analyzed whether tissue sodium content is increased in patients with type-2 diabetes (T2DM). Methods: Patients with T2DM were compared to those with primary hypertension. Patients with T2DM were off any antidiabetic and hypertensive patients off any antihypertensive therapy for at least 4 weeks. Skin and muscle sodium content was assessed non-invasively with a 3.0 T clinical MRI system (Magnetom Verio, Siemens Health Care, Erlangen, Germany)in each patient. Results: In patients with T2DM (N = 59)we observed significantly greater muscle sodium content (diabetes: 20.6 ± 3.5 vs hypertension: 16.3 ± 2.5 mmol/l, p < 0.001)and skin sodium content (diabetes: 24.5 ± 7.2 vs hypertension: 20.6 ± 5.7 mmol/l, p = 0.01)than in those with primary hypertension (N = 33). When potential confounders (age, body mass index, gender, systolic and diastolic blood pressure, estimated glomerular filtration rate)were entered in a covariance analysis, both skin sodium content (p = 0.037)and muscle sodium content (p < 0.001)were still clearly elevated. Conclusion: Patients with T2DM have greater skin and muscle sodium content. These are the first known data to demonstrate increased tissue sodium content in patients with T2DM, measured by 23 Na magnetic resonance imaging. Since tissue sodium content is related to organ damage, therapeutic intervention should aim at reducing tissue sodium content.
CRIS-Team Scopus Importer:2019-05-21
Keywords: 23Na-MRI; T2DM; Tissue sodium content; Salt; Sodium retention

Validation of semi-automated flow-mediated dilation measurement in healthy volunteers - Dobbie, Laurence J.; Mackin, Sharon T.; Hogarth, Katrina; Lonergan, Frances; Kannenkeril, Dennis; Brooksbank, Katriona; Delles, Christian (Blood Pressure Monitoring, 2020)
Background Flow-mediated dilation (FMD) is a non-invasive imaging modality used to measure endothelial function but has significant intra- and inter-observer variability. The use of semi-automated FMD devices could overcome this limitation. We assessed the reproducibility of same-day semi-automated FMD measurements by investigators who received basic training on the correct use of the device. Methods Forty-three healthy volunteers had two brachial artery FMD measurements performed 20 minutes apart using the UNEX EF 38G device, and automated outputs were produced. Images were also manually analysed using edge-detection software. The reproducibility of repeat FMD measurements within individuals was compared for automated and manual readings, and the correlation between analytical techniques was calculated. Results Twenty-five percent of scans were of non-diagnostic quality (n = 32). Automated analyses demonstrated sub-optimal reproducibility and measurement variability [intraclass correlation coefficient (ICCC) = 0.334, coefficient of variation (CV) = 45.87%]. In contrast, manually analysed scans had excellent reproducibility and low measurement variance (ICCC = 0.815, CV = 11.40%). FMD values obtained from automated and manual analysis correlated poorly (r = 0.164), whereas resting (r = 0.955) and maximal brachial artery diameters demonstrated excellent correlation (r = 0.867). Conclusion Manually evaluated serial UNEX EF readings have good reproducibility and therefore, the optimal FMD workflow involves manual analyses prior to independent automated interrogation. The high non-diagnostic scan rate is most likely the result of insufficient training and indicates that semi-automatic devices such as UNEX EF should be used by experienced investigators to achieve optimal results.
CRIS-Team Scopus Importer:2020-07-17
Keywords: cardiovascular risk; clinical research; endothelial function; flow-mediated dilation

VASCULAR REMODELING OF RETINAL VESSELS IN PATIENTS WITH CONGESTIVE HEART FAILURE - Jung, Susan; Kannenkeril, Dennis; Ott, Christian; Cifkova, R.; Harazny, J. M.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20